Follistatin-like 1: a novel biomarker with a potential link to obstructive sleep apnea severity and treatment efficacy - Alterki, Abdulmohsen; Abu-Farha, Mohamed; Al Shawaf, Eman; Alrashidi, Aldana; Alsuhail, Nouf; Al-Khairi, Irina; Cherian, Preethi; Madhu, Dhanya; Sriraman, Devarajan; Ebrahim, Mahmoud; Alterki, Mohammed; Bin-Hasan, Saadoun; et al. (Frontiers in Endocrinology, 2025)
IntroductionObstructive sleep apnea (OSA) is a common sleep disorder characterized by intermittent hypoxia, systemic inflammation, and metabolic dysfunction. Current diagnostic standards rely on polysomnography (PSG), which is limited by cost and accessibility. The identification of a sensitive and specific biomarker has the potential to aid both diagnosis and treatment monitoring. Follistatin-like 1 (FSTL1) has been implicated in inflammatory pathways; however, its role in OSA remains largely unexplored.Materials and MethodsIn this study, we aimed to explore changes in circulating FSTL1 levels in individuals with OSA to assess alterations following multilevel sleep surgery (MLS). We also evaluated its association with various metabolic and hypoxia-related markers, including Orexin-A, TNF-α, and IGFBP4. Our study was conducted at Dasman Diabetes Institute (DDI) in Kuwait through a cohort of 164 individuals, comprising 124 patients with OSA and 40 participants as non-OSA controls. Participants with OSA underwent MLS as a corrective intervention. A Type I polysomnography (PSG) test was performed in a level 1 sleep laboratory to diagnose sleep apnea. The apnea-hypopnea index (AHI) was measured at baseline and 3 months post-surgery to evaluate improvement in their condition.ResultsCirculating FSTL1 levels were significantly lower in individuals with OSA (10,245.53 ± 174.94; p < 0.001) compared to the control group (13,783.33 ± 688.69), with levels restored following surgery. Our data presented an inverse association between FSTL1 and AHI (p < 0.001), highlighting its potential use in reflecting OSA severity. Additionally, FSTL1 levels showed a significant negative correlation with the hypoxia-related marker IGFBP4 in OSA participants (r = –0.440; p = 0.005), suggesting a potential link to hypoxic regulation. FSTL1 levels increased significantly (p = 0.041) following MLS, coinciding with improvements in AHI and indicating remission of OSA. Further, the receiver operating curve (ROC) analysis emphasized a potential role for FSTL1 as a biomarker with predictive qualities for OSA, showing moderate diagnostic accuracy (AUC 0.73, 95% CI: 0.64–0.83, p < 0.001; 8819.09; sensitivity of 86.4%, specificity of 76.2%).ConclusionFSTL1 demonstrates potential as a valuable biomarker that can aid current diagnostic tools for OSA and help evaluate treatment efficacy; however, additional research is warranted to confirm its clinical applicability and explore its therapeutic potential.